CCS: Centro de Ciências da Saúde - Stefanon Bittencourt, Athelson; Vinícius Freitas Silva, Marcos; Favalessa Monteiro, Yuri; Veloso Menezes, Fabíola; Pavesi Miranda , Renan; Cadete da Penha, Marina; Margarida Romualdo, Kiara; Alves Zucheto, Natália; Alves de Oliveira , Dávilla; de Jesus da Costa França, Sara; da Silva Nogueiro, Magnus Matheus; Alves Viana, Walef; et al. (Revista Guará, 2023)
Resumos dos projetos do Centro de Ciências da Saúde